PERFOMANCE EVALUATION OF DYNAMIC LSA OPERATION THROUGH A MODEL OF A STAND-ALONE CELL - Mokrov, Evgeniy Vladimirovich; Gudkova, Irina Andreyevna (Современные информационные технологии и ИТ-образование; Том 12 № 1 (2016): Современные информационные технологии и ИТ-образование, 2016)
This paper considers an analytical model of an LTE network using LSA concept to gain access to the airport spectrum according to the limit power algorithm with signal-interference ratio threshold as a stand-alone cell during the airplane takeoff. User transmission power and transmission rate plots against time are presented for different cell locations for two different signal propagation models.